The global consumption and income project (GCIP): An overview - Rahul Lahoti; Arjun Jayadev; Sanjay Reddy (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2016)
We introduce two separate datasets (The Global Consumption Dataset (GCD) and The Global Income Dataset (GID)) making possible an unprecedented portrait of consumption and income of persons over time, within and across countries, around the world. The current benchmark version of the dataset presents estimates of monthly real consumption and income for every percentile of the population (a 'consumption/income profile') for more than 160 countries and more than half a century (1960-2015). We describe the construction of the datasets and demonstrate possible uses by presenting some sample results concerning the distribution of consumption, poverty and inequality in the world.
Keywords: B41; C80; I30; I32; O10; O15; 330; Consumption; Income; Growth; Global Income Distribution; Poverty; Inclusive Growth; Inequality